2007
DOI: 10.4049/jimmunol.179.2.1113
|View full text |Cite
|
Sign up to set email alerts
|

The Antiviral CD8+ T Cell Response Is Differentially Dependent on CD4+ T Cell Help Over the Course of Persistent Infection

Abstract: Although many studies have investigated the requirement for CD4+ T cell help for CD8+ T cell responses to acute viral infections that are fully resolved, less is known about the role of CD4+ T cells in maintaining ongoing CD8+ T cell responses to persistently infecting viruses. Using mouse polyoma virus (PyV), we asked whether CD4+ T cell help is required to maintain antiviral CD8+ T cell and humoral responses during acute and persistent phases of infection. Though fully intact during acute infection, the PyV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 73 publications
2
43
0
Order By: Relevance
“…Both CD4 + T cells and CD8 + T cells are well-characterized lymphocytes that respond to intracellular pathogens. The CD4 + is one of the surface markers of T helper (T H ) cells that participate in the adaptive immune responses, while CD8 + is expressed on cytotoxic T cells (CTLs), which are classified as a pre-defined cytotoxic role in the immune system [30]. CD4 + T cells appear critical in limiting pathogen further growth in the early stage of intracellular infection, whereas CD8 + T cells are particularly important in the later stage of infection [30].…”
Section: Discussionmentioning
confidence: 99%
“…Both CD4 + T cells and CD8 + T cells are well-characterized lymphocytes that respond to intracellular pathogens. The CD4 + is one of the surface markers of T helper (T H ) cells that participate in the adaptive immune responses, while CD8 + is expressed on cytotoxic T cells (CTLs), which are classified as a pre-defined cytotoxic role in the immune system [30]. CD4 + T cells appear critical in limiting pathogen further growth in the early stage of intracellular infection, whereas CD8 + T cells are particularly important in the later stage of infection [30].…”
Section: Discussionmentioning
confidence: 99%
“…CD8 memory T cells formed in animals that lack CD4 T cells contain a larger than usual population of terminally diVerentiated cells that are deWcient in their recall responses, and these "unhelped" memory CD8 T cells tend to decay over time for reasons that are not perfectly understood [58][59][60][61][62][63]. Under certain conditions, activation of CD8 T cells without CD4 T cell help increases the expression of the TNF-family receptor TRAIL, which may induce the apoptosis of these "unhelped" CD8 T cells and diminish their ability to re-expand [60,64].…”
Section: Antigen and Tcr Signalingmentioning
confidence: 99%
“…PyV elicits both CD4 T-cell-dependent and -independent antiviral humoral responses, which, while promoting viral clearance, are not sufficient to prevent PyV tumorigenesis (1,13,27,37,38). We recently reported that MHC-II-deficient B6 mice, which maintain a small, chronic memory PyV-specific CD8 T-cell population, do not develop PyV-induced tumors (22); thus, even a small functional MHC-I-restricted T-cell response, as seen in the LR-CD8KO mice, would also likely be sufficient for PyV tumor resistance. Nevertheless, 20 to 30% of PyV-infected CD8KO mice have previously been reported to develop hind limb paralysis (13), which is associated with PyV-induced vertebral tumors (19,41).…”
mentioning
confidence: 99%